Stage of Fruit Maturity on Seed Quality during Storage in Tomato (Lycopersicon esculentum Mill.) - H.S.YOGEESHA; K.BHANU PRAKASH; L.B.NAIK (Seed Research, 2026)
For seed purpose, tomato fruits are harvested at red ripe stage and the fruit picking is a continuous process as the fruits mature over a period of time. A study was conducted with an indeterminate tomato cv. Arka Vikas to know the feasibility of harvesting fruits at different maturity stages so as to reduce the number of fruit pickings. Fruits were picked at various stages starting from mature green to over ripe soft stage and the seeds were extracted on the day of harvest. There was no significant difference among fruit maturity stages on seed germination when assessed at 2 months after extraction. The germination was above 93% in all the cases. However, the seed extracted from mature green fruits had significantly lower test weight, poor seed lustre, decreased root length and vigour index compared to others. Same trend was noticed during storage under ambient conditions up to 10 months, without any significant reduction in germination. At the end of 14th month of storage a slight reduction in germination was observed in all fruit maturity stages except for seeds from over ripe firm fruits and it remained so up to 18th month. However, differences among various maturity group for seed quality was obvious at the end of 22nd month of storage. Only seeds extracted from over ripe firm fruits maintained germination above 85% at the end 22nd month of stroage.